Optimum Rotation of Harvest for Poplars in Farmlands under Agroforestry - Chaturvedi, A. N. (Indian Forester, 1992)
The paper gives an account of a case study of Poplar grown by a farmer in December, 1983. Poplars have been successfully iocroporated in agroforestry plantations in U.P., Haryana and Punjab. Some of the clones successful are G-3, G-48, D-121, ST-67 etc. The spacing of 5Ã—5m has given good results and closer than 4Ã—4 m have not produced desired results. The results of case study shows that highest IRR is obtainable in the fourth year and the IRR goes down in the 7th year. A rotation of 4 years is viable for Poplar where there is local demand for small size. It is, however, expected that increasing use of Poplar wood for plywood will push up the price for large size trees and profitability will increase for rotations of 9 years or more.